Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

I'm struggling on finding a step-through for this question, can anyone help? (x+5)(2x+3)-3(x-2)(6x+5)

Sagot :

[tex]~~(x+5)(2x+3)-3(x-2)(6x+5)\\\\=2x^2 +3x + 10x +15 - (3x-6)(6x+5)\\\\=2x^2 +13x +15 - (18x^2 +15x -36x -30)\\\\=2x^2+13x+15-(18x^2 -21x-30)\\\\=2x^2 +13x+15-18x^2 +21x +30\\\\=-16x^2 + 34x+45[/tex]